Pengaruh Orientasi Pembelajaran, Kemampuan Produksi, dan Orientasi Pasar Terhadap Strategi Bisnis dan Kinerja Bisnis - Sutanto, J.E. (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2009)
One indicator of companyÃ¢â‚¬â„¢s or businessÃ¢â‚¬â„¢s successfulness in the competition was the companyÃ‚Â or business must have competitive advantage that allowed the industrial company of foods andÃ‚Â beverages yielding the superiority of production result than their competitors in the determiningÃ‚Â the strategy and business performance continually. Ã‚Â The population of this research was foodsÃ‚Â and Ã‚Â beverages Ã‚Â industry Ã‚Â especially Ã‚Â big Ã‚Â and Ã‚Â medium Ã‚Â industrial company, Ã‚Â which Ã‚Â have Ã‚Â multi-business Ã‚Â and Ã‚Â multi-products Ã‚Â in Ã‚Â the Ã‚Â East Ã‚Â Java area Ã‚Â that Ã‚Â consist Ã‚Â of Ã‚Â 1286 Ã‚Â industrial Ã‚Â companiesÃ‚Â of Ã‚Â foods Ã‚Â and Ã‚Â beverages according Ã‚Â to Ã‚Â the Ã‚Â Indonesian Ã‚Â Business Ã‚Â Field Ã‚Â Classification Ã‚Â Ã‚Â (KLUI Ã‚Â 15)Ã‚Â years 2002. Ã‚Â The Ã‚Â data Ã‚Â analysis Ã‚Â technique Ã‚Â used Ã‚Â Structural Ã‚Â Equation Ã‚Â Modeling Ã‚Â = SEM) Ã‚Â withÃ‚Â computer Ã‚Â help Ã‚Â used Ã‚Â AMOS Ã‚Â program Ã‚Â 4.0 Ã‚Â version.The Ã‚Â research result Ã‚Â indicated Ã‚Â that: Ã‚Â (1) Ã‚Â all Ã‚Â ofÃ‚Â independent variables have positive influence and significant toward the business strategy andÃ‚Â the business performance; (2) simultaneously the influence of teaching orientation, productionÃ‚Â competence Ã‚Â and Ã‚Â market Ã‚Â orientation Ã‚Â toward Ã‚Â business Ã‚Â strategy and Ã‚Â business Ã‚Â performance Ã‚Â wasÃ‚Â proper as the created model. Ã‚Â The conclusion of this research was the research result generallyÃ‚Â indicated Ã‚Â the Ã‚Â existence ofÃ‚Â positive Ã‚Â influence Ã‚Â that Ã‚Â experienced Ã‚Â by Ã‚Â that Ã‚Â industrial Ã‚Â company Ã‚Â ofÃ‚Â foods and beverages both from test result partially or simultaneously. And that not all of partialÃ‚Â or simultaneous influence toward business strategy and business performance has positive orÃ‚Â negative result, but it still categorized as reasonable.